2015
DOI: 10.1186/s12889-016-2762-1
|View full text |Cite
|
Sign up to set email alerts
|

Psycho-social resilience, vulnerability and suicide prevention: impact evaluation of a mentoring approach to modify suicide risk for remote Indigenous Australian students at boarding school

Abstract: BackgroundThe proposed study was developed in response to increased suicide risk identified in Aboriginal and Torres Strait Islander students who are compelled to attend boarding schools across Queensland when there is no secondary schooling provision in their remote home communities. It will investigate the impact of a multicomponent mentoring intervention to increase levels of psychosocial resilience. We aim to test the null hypothesis that students’ resilience is not positively influenced by the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Many tribal youth struggle with these issues. It would be important to also engage community resources for support, including working with community leaders, teachers, and American Indian college students as mentors . School screenings for at‐risk students could be conducted in collaboration with tribal organizations.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…Many tribal youth struggle with these issues. It would be important to also engage community resources for support, including working with community leaders, teachers, and American Indian college students as mentors . School screenings for at‐risk students could be conducted in collaboration with tribal organizations.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…This study focuses on the health, healthcare service use and satisfaction of a cohort of Indigenous remote-dwelling north Queensland students who are required to attend boarding schools for secondary education because there is limited or no secondary schooling available in their home communities. It forms part of a broader ecological study to support and enhance the resilience of these students; other papers have provided a study protocol [22], descriptions of the survey development and validation [23,24], description of staff capacity development [25] and student survey baseline results [26]. Anecdotal evidence (2016) attained through this broader resilience study suggested that some students had untreated health conditions upon arrival at or during boarding school education, and/or experienced patchy care between remote home community and schoolbased healthcare services.…”
Section: Research and Theorymentioning
confidence: 99%
“…Informed by research (2015-2016), the service is shifting to an ecological, resilience-focused 1 Traditional place of family origin. approach (Kitchener and Jorm, 2008;Tsey et al, 2010;Ungar and Liebenberg, 2011;McCalman et al, 2016). In addition to working with students, TSS staff engage with families, boarding schools, and partner services to support students' adjustment, orientation, and students' ongoing stay at boarding school.…”
Section: Transition To Secondary Schoolsmentioning
confidence: 99%
“…The 5-year Resilience Study was developed in partnership with TSS in response to identified self-harm and suicide risk for transitioning students (McCalman et al, 2016). It was funded by the National Health and Medical Research Council from December 2014.…”
Section: The Resilience Studymentioning
confidence: 99%
See 1 more Smart Citation